(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, it is considered that folklore is an art that has been collected by a certain nation over the centuries, embodies the national characteristics of that nation, and whose origins go back to ancient times. It is emphasized that each of its types reflects the feelings, character, dreams, customs and traditions of the creators, as well as from the living climate to the nature. Information is provided about proverbs, one of the folk oral genres that have such characteristics. National-cultural features specific to proverbs in the translation of proverbs are also highlighted.